Trade-off between Performance and Security for Supersingular Isogeny-Based Cryptosystems - Téllez, Claudio; Borges, Fábio (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2018)
Cryptosystems based on isogenies between supersingular elliptic curves are considered promising candidates for a post-quantum era. Their security is based on the intractability of the Computational Supersingular Isogeny Problem (CSSIP) and of the Decisional Supersingular Product Problem (DSSPP). For this reason, there have been many important breakthroughs in supersingular isogeny cryptography in recent years. The purpose of our work is to provide a complexity analysis of the trade-off between performance and security for supersingular isogeny-based cryptosystems (SSI) in comparison with Discrete Logarithm Problem (DLP) and Integer Factorization Problem (IFP). We show how the complexities increase for the attack algorithms when the key lengths become longer. As SSI achieves small key sizes at practical security levels, it is a strong potential quantum-resistant cryptosystem.